Straightforward Synthesis of Functionalized Furo[3,4-d]pyrimidine-2,4-diones - De Coen, Laurens M.; Jatczak, Martyna; Muylaert, Koen; Mangelinckx, Sven; Stevens, Christian V. (Synthesis, 2015)
An efficient synthesis of furo[3,4-d]pyrimidine-2,4-diones has been accomplished via a straightforward three-step pathway. Curtius rearrangement of 4-(methoxycarbonyl)furan-3-carboxylic acid and subsequent reaction with a variety of amines resulted in the corresponding intermediate ureids, which could be ring closed to the bicyclic scaffold in good yields. Functionalization of N-1 afforded a small library of new heterocycles. (Partial) hydrogenation of the furo[3,4-d]pyrimidine-2,4-diones led to the 5,7-dihydro- and tetrahydrofuro[3,4-d]pyrimidine-2,4-diones.
Keywords: heterocycles; ring closure; alkylation; rearrangement; hydrogenation